Experimental study of the piezoelectricity of Middle Pleistocene loess in the Weibei region, China - Yanlin JING; Jie LIU; Qingying LIU; Xiaoxiao DUAN; Na XIE; Dengke YANG (Meitian dizhi yu kantan)
ObjectiveQuartz, the piezoelectric material discovered the earliest, has found widespread applications in industry, military fields, and daily life due to its piezoelectricity. The widely distributed loess worldwide is composed primarily of quartz, accounting for 37.0% to 69.9%. However, there is a lack of studies on the piezoelectricity of loess both domestically and internationally. MethodsThis study investigated the \begin{document}${Q}_2^{{eol}} $\end{document} loess from the Weibei Loess Tableland in Shaanxi Province as an example to explore the piezoelectricity of loess. The piezoelectric coefficient of the loess was measured, and its piezoelectric voltage under the action of static loading and vibration was investigated using experiments Results and Conclusions The results indicate that loess exhibits piezoelectricity. Based on this characteristic, loess can be used for developing piezoelectric cells and conduct piezoelectric power generation. The piezoelectricity of loess is related to its dry density and moisture content rather than its thickness. Loess with lower dry density and higher moisture content exhibits stronger piezoelectricity and a higher piezoelectric coefficient; and vice versa. Under the conditions of natural density and moisture content, loess exhibits a piezoelectric coefficient of 16.1 pC/N. Under the action of static loading, the piezoelectric voltage signals of the loess appeared as a sine wave with regular waveforms, a frequency of 10 MHz, a period of 100 ns, and piezoelectric voltage exceeding 0.6 V. When multiple loess samples were connected in series, the voltage increased cumulatively. Under the action of vibration, the piezoelectric voltage of the loess increased significantly. It variedunder different vibration frequencies and peaked under resonance, with the maximum voltage of a single loess sample exceeding 2.1 V. Investigating the feasibility of replacing traditional car batteries with loess-based piezoelectric cells under the combined action of vibration and upper load is undoubtedly a topic of great interest. Furthermore, research based on the piezoelectricity of loess in loess regions, including soil moisture monitoring, seismic activity monitoring, and predominant period determination, holds great theoretical and practical significance. The results of this study could serve as a valuable reference for these research in loess areas.